Introduction and elimination of Bovine Viral Diarrhoea Virus in a commercial beef herd: a case study. Issue 12 (21st September 2020) - Allworth, MB; Long, R; Smith, AK; Bergman, EL; Hernandez‐Jover, M
Abstract : Routine Bovine Viral Diarrhoea Virus (BVDV) monitoring of a commercial beef herd in southern New South Wales over a 10‐year period provided an opportunity to assess the impact of the introduction of BVDV on that herd. BVDV antibody testing provided strong evidence that the herd was initially free of BVDV (2009–2011). Testing from 2012 suggested BVDV had been introduced into the herd and this was confirmed in 2015 with the identification of persistently infected (PI) animals. Having become established in the herd, the owners then set out to eliminate BVDV from the herd. Antigen testing aimed at identifying PI animals revealed BVDV was already absent from the herd. Subsequent antibody testing confirmed that the herd was now free from BVDV. Despite the incursion of BVDV in this herd, there was little measurable impact on reproductive performance (pregnancy rates), although suspected increased calf losses from birth to calf marking were reported. This is the first time such self‐clearance has been documented as part of a longitudinal study under Australian conditions.